Effects of fulvic acid and montmorillonite colloids at different concentrations on Cd(II) sorption onto nano-hydroxyapatite. (June 2020) - Wu, Mengmeng; Mo, Limei; Bi, Erping
Abstract: Natural colloids can influence the binding mechanisms between nano-hydroxyapatite (nHAP) and Cd(II). In this study, the effects of organic and inorganic natural colloids on Cd(II) sorption onto nHAP were compared. Different experimental approaches combined with the additivity model and the Extended-Derjaguin-Landau-Verwey–Overbeek model were used to quantify the distribution of Cd(II) in the systems of nHAP and natural colloid, and the interaction energy between particles. The results showed that both fulvic acid (FA) and montmorillonite colloid (MONT) had the promotion and inhibition effects on Cd(II) sorption onto nHAP. Coexistence of FA or MONT could stabilize nHAP particles. FA could adsorb onto nHAP particle surface via carboxylic and phenolic groups, which increased nHAP electronegativity and formed steric resistance effect. Coexistence of MONT mainly increased nHAP electronegativity. These effects prevented the reduction of the specific surface area of nHAP particles and increased the Cd(II) sorption onto nHAP. However, the inhibition effect on Cd(II) sorption was enhanced with increasing concentration of FA or MONT because more soluble FA-Cd or suspended MONT-Cd complexes formed in the system. In nHAP-FA-Cd systems, the Cd(II) sorption onto FA was well predicted but that onto solid phase was underestimated by the additivity model. In nHAP-MONT-Cd systems, Cd(II) sorbed onto mixtures of nHAP and MONT was well described by the additive model. The findings of this study can help to understand the fate of Cd(II) in natural water and soil. Graphical abstract: Image 1 Highlights: Binding of FA to nHAP prevents its aggregation and increases its electronegativity. Montmorillonite increases Cd sorption onto nHAP mainly due to electrostatic forces. Soluble FA-Cd complex and suspended montmorillonite-Cd inhibit Cd sorption onto nHAP. The additive model applied in nHAP-FA mixtures underestimates Cd sorption onto nHAP. Cd adsorbed onto nHAP-montmorillonite mixtures is well described in additive model.